2013
DOI: 10.3389/fpsyg.2013.00988
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of internalizing disorders in 9–10 year old children: efficacy of the Aussie Optimism Positive Thinking Skills Program at 30-month follow-up

Abstract: The Aussie Optimism: Positive Thinking Skills Program (AOPTP) is a school-based prevention program aimed at addressing anxious and depressive symptoms in children aged 9-10 years. Nine-hundred and ten students from 22 Australian primary schools situated in low socio-economic areas were randomly assigned to either an intervention or control group, and assessed at a 30-month follow up. Those in the intervention group received the AOPTP program, where the control group continued to receive the regular health educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 64 publications
(73 reference statements)
4
19
1
4
Order By: Relevance
“…The finding of reduced hyperactivity in the primary analysis was consistent with Rooney and colleague's findings (Morrison et al, 2013) and findings from the secondary analysis which found no significant difference between intervention and control children on parent reported Hyperactivity, Emotion, Conduct or Peer Relation problems were not consistent with Rooney et al (2013), Morrison et al (2013). On the other hand, the finding from the secondary analysis indicating an increase in peer-related problems was not consistent with Lacey et al (submitted).…”
Section: Discussionsupporting
confidence: 83%
“…The finding of reduced hyperactivity in the primary analysis was consistent with Rooney and colleague's findings (Morrison et al, 2013) and findings from the secondary analysis which found no significant difference between intervention and control children on parent reported Hyperactivity, Emotion, Conduct or Peer Relation problems were not consistent with Rooney et al (2013), Morrison et al (2013). On the other hand, the finding from the secondary analysis indicating an increase in peer-related problems was not consistent with Lacey et al (submitted).…”
Section: Discussionsupporting
confidence: 83%
“…For the purposes of the current study, the combination of complex abstract material, delivered at an age of concrete cognitive style, in the absence of repeated opportunities to consolidate the skills, in conjunction with the small sample size due to attrition, may underlie the failure to observe any benefits from this program at 42 and 54 month follow-up. This is not to suggest that the program does not have the potential for effectiveness in minimising risk of internalizing disorders: indeed benefits were reported immediately at post-intervention, 6 and 30 months follow-up (Morrison et al, 2013; Rooney et al, 2013), suggesting they were able to benefit from the program in the short and medium term. The results do suggest that future programs should consider the following: (i) modifying the complexity of the content to better suit the concrete cognitive style for younger children; (ii) revisit the content materials after 6-month lapse to revise the social and emotional skills learned.…”
Section: Resultsmentioning
confidence: 93%
“…The 10-week AOP-PTS program was delivered to 8–9 year old children in years 4–5 of primary school, with follow-up assessment of internalizing symptoms and attributional styles conducted at 42 and 54 months post intervention. Data were also collected at 6 and 18 and 30 months post-intervention (Rooney et al, 2013; Morrison et al, 2013). Of these previous studies, the AOP-PTS program was found to be associated with reduced in depression symptoms at post-test, emotional difficulties at 6 months post-intervention but not at 18 months follow-up, and less hyperactive at 30 months follow-up (Morrison et al, 2013; Rooney et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations